2019
DOI: 10.1074/jbc.ra119.011549
|View full text |Cite|
|
Sign up to set email alerts
|

Cultivation at high osmotic pressure confers ubiquinone 8–independent protection of respiration onEscherichia coli

Abstract: Ubiquinone 8 (coenzyme Q8 or Q8) mediates electron transfer within the aerobic respiratory chain, mitigates oxidative stress, and contributes to gene expression in Escherichia coli. In addition, Q8 was proposed to confer bacterial osmotolerance by accumulating during growth at high osmotic pressure and altering membrane stability. The osmolyte trehalose and membrane lipid cardiolipin accumulate in E. coli cells cultivated at high osmotic pressure. Here, Q8 deficiency impaired E. coli growth at low osmotic pres… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(1 citation statement)
references
References 74 publications
0
1
0
Order By: Relevance
“…Well defined osmoregulatory systems respond by mediating solute synthesis or the uptake of exogenous osmolytes to restore cellular hydration. Osmosensing transporters like ProP and ProVWX activate to mediate osmolyte uptake as other transporters inactivate at high osmotic pressure [ 40 ]. It showed that E. coli protein ProP is both an osmosensor and an osmoprotectant transporter [ 41 ].…”
Section: Discussionmentioning
confidence: 99%
“…Well defined osmoregulatory systems respond by mediating solute synthesis or the uptake of exogenous osmolytes to restore cellular hydration. Osmosensing transporters like ProP and ProVWX activate to mediate osmolyte uptake as other transporters inactivate at high osmotic pressure [ 40 ]. It showed that E. coli protein ProP is both an osmosensor and an osmoprotectant transporter [ 41 ].…”
Section: Discussionmentioning
confidence: 99%